2018
DOI: 10.1259/bjr.20170977
|View full text |Cite
|
Sign up to set email alerts
|

The impact of contrast-enhanced spectral mammogram (CESM) and three-dimensional breast ultrasound (3DUS) on the characterization of the disease extend in cancer patients

Abstract: CESM is a recommended investigation in breast cancer to increase the accuracy of size measurement and the detection of multiple tumors. The addition of 3D ultrasound can enhance the detection of intraductal extension. Advances in knowledge: Choice of conservative breast surgery vs mastectomy is still a debate. We used an advanced, contrast-based, application of the mammogram: CESM and a non-invasive 3D breast ultrasound in the assessment of the local extension of the breast cancer regarding size, perifocal str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…[ 15 ] Several studies proved that the diagnostic accuracy of CESM is comparable to that of MRI. [ 7 , 8 , 9 , 10 ] In addition, CESM has a shorter examination time, no noise, and a lower cost. It is especially suitable for patients with contraindications of breast MR examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 15 ] Several studies proved that the diagnostic accuracy of CESM is comparable to that of MRI. [ 7 , 8 , 9 , 10 ] In addition, CESM has a shorter examination time, no noise, and a lower cost. It is especially suitable for patients with contraindications of breast MR examination.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Helal et al reported that CESM had higher sensitivity, specificity and accuracy than DM+2-dimensional ultrasound (2DUS). [ 7 ] Several studies proved that CESM has the same diagnostic accuracy as breast MRI, and its specificity is even better than that of MRI. [ 8 , 9 , 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…So, three-dimensional US technology was developed for three-dimensional imaging of tumour morphology and blood vessel distribution, which are shown when patients are diagnosed. 30 The colour Doppler US is one of many three-dimensional US and can clearly reflect the situation of tumour and blood flow information and provide doctors with more valuable clinical information, so that it can distinguish benign and malignant tumours. 31 In 1998, Krouskop 32 found that there are elastic differences in different tissues, which provides theoretical foundation for developing elastic US.…”
Section: Ultrasonographymentioning
confidence: 99%
“…Surely, the two‐dimensional US only gets some flat images of tumour, and judgement by physicians will be affected. So, three‐dimensional US technology was developed for three‐dimensional imaging of tumour morphology and blood vessel distribution, which are shown when patients are diagnosed 30 . The colour Doppler US is one of many three‐dimensional US and can clearly reflect the situation of tumour and blood flow information and provide doctors with more valuable clinical information, so that it can distinguish benign and malignant tumours 31 .…”
Section: Imaging Diagnosismentioning
confidence: 99%
“…In the future, MG is likely to become safer and offer higher resolution. Moreover, advancements in artificial intelligence (AI) and sensor technology could enable automated breast cancer detection and analysis (Helal et al, 2018).…”
Section: Mammographymentioning
confidence: 99%